A Metabolic Screen in Adolescents Reveals an Association Between Circulating Citrate and Cortical Bone Mineral Density. (18th March 2019) - Kemp, John P; Sayers, Adrian; Fraser, William D; Davey Smith, George; Ala‐Korpela, Mika; Evans, David M; Tobias, Jonathan H
ABSTRACT: Observations that insulin and adiponectin levels are related to cortical bone size in adolescents, independently of body composition, suggest factors related to fat metabolism directly influence skeletal development. To explore this question, we examined associations between a metabolic screen focusing on fat metabolism, and peripheral quantitative computed tomography (pQCT) measures of the mid‐tibia, in 15‐year‐olds from the Avon Longitudinal Study of Parents and Children. Metabolic profiles were generated by proton nuclear magnetic resonance spectroscopy, from blood samples obtained at the same time as pQCT scans. Ordinary least squares linear regression was used to investigate relationships between metabolic measures and periosteal circumference (PC), cortical thickness (CT), and cortical bone mineral density (BMDC ). Metabolic profiles yielded 22 independent components following principal component analysis (PCA), giving a Bonferroni‐adjusted threshold for statistical significance of p = 0.002. Data were available in 1121 subjects (487 males), mean age 15 years. Several metabolites related to lipid and cholesterol metabolism were associated with PC, CT, and BMDC after adjustment for age, sex, and Tanner stage. After additional adjustment for height, fat, and lean mass, only the association between citrate and BMDC remained below the Bonferroni‐significant threshold (β = –0.14 [–0.18, –0.09]) (β represents a standardized coefficient). Citrate also showed evidence of association with PC (β = 0.06 [0.03, 0.10]) and strength strain index (SSI; β = 0.04 [0.01, 0.08]). Subsequently, we investigated whether these relationships were explained by increased bone resorption. Citrate was strongly related to serum β‐C‐telopeptides of type I collagen (β‐CTX) (β = 0.20 [0.16, 0.23]). After additional adjustment for β‐CTX the above associations between citrate and BMDC (β = –0.04 [–0.08, 0.01]), PC (β = 0.03 [–0.01, 0.07]) and SSI (β = 0.03 [–0.01, 0.07]) were no longer observed. We conclude that in adolescents, circulating levels of citrate are inversely related to BMDC and positively related to PC, reflecting associations with higher bone turnover. Further studies are justified to elucidate possible contributions of citrate, a constituent of bone matrix, to bone resorption and cortical density. © 2019 American Society for Bone and Mineral Research.